2018
DOI: 10.1111/cmi.12829
|View full text |Cite
|
Sign up to set email alerts
|

Filifactor alocismodulates human neutrophil antimicrobial functional responses

Abstract: Filifactor alocis is a newly appreciated pathogen in periodontal diseases. Neutrophils are the predominant innate immune cell in the gingival crevice. In this study, we examined modulation of human neutrophil antimicrobial functions by F. alocis. Both non-opsonised and serum-opsonised F. alocis were engulfed by neutrophils but were not efficiently eliminated. Challenge of neutrophils with either non-opsonised or serum-opsonised F. alocis induced a minimal intracellular as well as extracellular respiratory burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 70 publications
4
44
0
1
Order By: Relevance
“…Together, this data shows that F. alocis challenge induces temporal changes in neutrophil functional mechanisms like cytokine production, chemotaxis, vesicular trafficking, and degranulation, as well as neutrophil biochemical mechanisms like the regulation of signaling pathways and metabolism. This coincides with previous data from our laboratory that shows that F. alocis affects neutrophil cytokine production, chemotaxis, vesicle trafficking, and degranulation functions (21,22).…”
Section: F Alocis Affects Neutrophil Functional and Biochemical Procsupporting
confidence: 93%
See 1 more Smart Citation
“…Together, this data shows that F. alocis challenge induces temporal changes in neutrophil functional mechanisms like cytokine production, chemotaxis, vesicular trafficking, and degranulation, as well as neutrophil biochemical mechanisms like the regulation of signaling pathways and metabolism. This coincides with previous data from our laboratory that shows that F. alocis affects neutrophil cytokine production, chemotaxis, vesicle trafficking, and degranulation functions (21,22).…”
Section: F Alocis Affects Neutrophil Functional and Biochemical Procsupporting
confidence: 93%
“…However, oral pathogens have evolved mechanisms to manipulate neutrophil functional responses to prevent being killed while propagating inflammation (17,19). Previous work from our laboratory has shown that despite efficient phagocytosis by neutrophils, F. alocis survives within neutrophils by inducing minimal production of intracellular ROS and curtailing the fusion of antimicrobial granules with its phagosome (20,21). However, in comparison to the keystone oral pathogen, P. gingivalis, and another emerging oral pathogen, Peptoanaerobacter stomatis, challenge with F. alocis resulted in a mild release of neutrophil-derived proinflammatory cytokines, which resulted in limited recruitment of monocytes and other neutrophils (22).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the immediate pattern of exocytosis of human neutrophil granules is unique to M. smegmatis. While other bacteria have been shown to block or induce degranulation of some or all neutrophil granule subtypes [32,[49][50][51][52][53][54][55][56][57][58][59], release of only gelatinase granules at early time points has not been seen with bacteria other than M. smegmatis. An important distinction is that M. smegmatis is not preventing granule release to other stimuli, since granule mobilization was not affected upon fMLF stimulation by human neutrophils cultured with M. smegmatis.…”
Section: Discussionmentioning
confidence: 99%
“…1 As one of the first lines of defence, they are essential in the response to pathogen invasion. 3 Neutrophils receive an innovative pattern of apoptosis programing signals known as NETosis that induces the release of neutrophil extracellular traps (NETs), which are composed of double-stranded DNA resembling a net with a histone coating as well as antimicrobial agents including myeloperoxidase. 3 Neutrophils receive an innovative pattern of apoptosis programing signals known as NETosis that induces the release of neutrophil extracellular traps (NETs), which are composed of double-stranded DNA resembling a net with a histone coating as well as antimicrobial agents including myeloperoxidase.…”
Section: Introductionmentioning
confidence: 99%
“…2 They eradicate bacteria via phagocytosis or by releasing antimicrobial proteins in degranulation. 3 Neutrophils receive an innovative pattern of apoptosis programing signals known as NETosis that induces the release of neutrophil extracellular traps (NETs), which are composed of double-stranded DNA resembling a net with a histone coating as well as antimicrobial agents including myeloperoxidase. 4,5 NETs attract and eradicate bacteria and counteract viruses.…”
Section: Introductionmentioning
confidence: 99%